Traditional Chinese Exercises on Pain and Disability in Middle-Aged and Elderly Patients With Neck Pain: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Kong, Lingjun; Ren, Jun; Fang, Sitong; He, Tianxiang; Zhou, Xin; Fang, Min (Frontiers in Aging Neuroscience, 2022)
Background With the change of life and work style, more middle-aged and elderly individuals are suffering neck pain. In China, traditional Chinese exercises are widely used in the management of neck pain, including Tai Chi, Qigong, Yijinjing, Baduanjin, Liuzijue, and Five-animal exercises. However, the evidence of traditional Chinese exercises for neck pain maintains controversial. Therefore, the current systematic review was conducted to evaluate the effects of traditional Chinese exercises on pain and disability of middle-aged and elderly patients with neck pain. Methods A comprehensive literature search was performed in six electronic databases from their inception to January 2022 for randomized controlled trials of traditional Chinese exercises for neck pain. The methodological quality of the included studies was assessed by PEDro scale. The subgroup analysis was conducted based on different traditional Chinese exercises. The I2 statistic was applied to assess the heterogeneity. Results Twenty-one studies were included in our review, which were conducted in China, USA and Germany between 2003 and 2021. Most (86%) of them exceeded the cut off score 6. Traditional Chinese exercises included Baduanjin, Yijinjing, Tai Chi, Qigong and Five-animal exercises. The aggregated results indicated that traditional Chinese exercises showed positive complementary effects in relieving pain (SMD, 1.12; 95% CI, 0.78 to 1.45; P<0.00001), especially Baduanjin exercises. Baduanjin exercises also showed beneficial complementary effects in improving flexion (SMD, 0.65; 95% CI, 0.28 to 1.03; P=0.0006) and extension (SMD, 0.66; 95% CI, 0.12 to 1.19; P=0.02) of the neck. In addition, the aggregated results indicated that traditional Chinese exercises alone showed beneficial effects in improving disability (SMD, 0.74; 95% CI, 0.40 to 1.08; P<0.0001) and relieving pain (SMD, 0.81; 95% CI, 0.50 to 1.13; P<0.00001) compared with waiting list. The follow-up effects of traditional Chinese exercises were still insufficient. Conclusions There was the positive evidence to support the clinical use of traditional Chinese exercises, as a complementary therapy, for middle-aged and elderly patients with neck pain, especially Baduanjin exercises. However, the evidence supporting the effects of traditional Chinese exercises alone for the middle-aged and elderly patients with neck pain was limited due to the small sample size.